Sex differences in cognitive resilience in preclinical autosomal‐dominant Alzheimer's disease carriers and non‐carriers: Baseline findings from the API ADAD Colombia Trial. Issue 11 (1st February 2022) - Vila‐Castelar, Clara; Tariot, Pierre N.; Sink, Kaycee M.; Clayton, David; Langbaum, Jessica B.; Thomas, Ronald G.; Chen, Yinghua; Su, Yi; Chen, Kewei; Hu, Nan; Giraldo‐Chica, Margarita; Tobón, Carlos; et al.
Abstract: Introduction: Females may have greater susceptibility to Alzheimer's disease (AD)‐pathology. We examined the effect of sex on pathology, neurodegeneration, and memory in cognitively‐unimpaired Presenilin‐1 ( PSEN1 ) E280A mutation carriers and non‐carriers. Methods: We analyzed baseline data from 167 mutation carriers and 75 non‐carriers (ages 30 to 53) from the Alzheimer's Prevention Initiative Autosomal Dominant AD Trial, including florbetapir‐ and fludeoxyglucose‐PET, MRI based hippocampal volume and cognitive testing. Results: Females exhibited better delayed recall than males, controlling for age, precuneus glucose metabolism, and mutation status, although the effect was not significant among PSEN1 mutation carriers only. APOE ε4 did not modify the effect of sex on AD biomarkers and memory. Discussion: Our findings suggest that, among cognitively‐unimpaired individuals at genetic risk for autosomal‐dominant AD, females may have greater cognitive resilience to AD pathology and neurodegeneration than males. Further investigation of sex‐specific differences in autosomal‐dominant AD is key to elucidating mechanisms of AD risk and resilience.